2011
DOI: 10.1016/j.ab.2010.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of immobilized cannabinoid receptor (CB1/CB2) open tubular column for on-line screening

Abstract: Cannabinoid Receptors, CB1 and CB2, are therapeutic targets in the treatment of anxiety, obesity, movement disorders, glaucoma and pain. We have developed an on-line screening method for CB1 and CB2 ligands, where cellular membrane fragments of a chronic myelogenous leukemia cell line, (KU-812), were immobilized onto the surface of an open tubular capillary to create a CB1/CB2-OT column. The binding activities of the immobilized CB1/CB2 receptors were established using frontal affinity chromatographic techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…Since the successful immobilization of nAChRs on the IAM stationary phase, multiple transmembrane proteins have been used to prepare CMACs with IAM.PC (immobilized artificial membrane phosphatidylcholine). The examples of transmembrane proteins immobilized on IAM.PC particles include: ligand-gated ion channels ( x  y nAChR x = 3,4,7; y = 2,3,4; GABA A , NMDA, combination of nAChR, NMDA) [11,13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], G-protein coupled receptors (opioid, -adrenergic, P2Y1, Histamine 1-4, CB 1 , CB 2 ) [31][32][33][34][35] and drug transporters (ABC: Pgp, MRP1, MRP2, BCRP; SLC: hOCT and hOCT SNPs, hOAT) [36][37][38][39]. IAM.PC mimics the cell membrane environment and keeps the experimental conditions close to the physiological state.…”
Section: Cellular Membrane Affinity Chromatography Columns -A Short Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the successful immobilization of nAChRs on the IAM stationary phase, multiple transmembrane proteins have been used to prepare CMACs with IAM.PC (immobilized artificial membrane phosphatidylcholine). The examples of transmembrane proteins immobilized on IAM.PC particles include: ligand-gated ion channels ( x  y nAChR x = 3,4,7; y = 2,3,4; GABA A , NMDA, combination of nAChR, NMDA) [11,13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], G-protein coupled receptors (opioid, -adrenergic, P2Y1, Histamine 1-4, CB 1 , CB 2 ) [31][32][33][34][35] and drug transporters (ABC: Pgp, MRP1, MRP2, BCRP; SLC: hOCT and hOCT SNPs, hOAT) [36][37][38][39]. IAM.PC mimics the cell membrane environment and keeps the experimental conditions close to the physiological state.…”
Section: Cellular Membrane Affinity Chromatography Columns -A Short Hmentioning
confidence: 99%
“…Lipophilic compounds have been found to be strongly retained on IAM.PC particles and an alternative approach has been proposed to study such ligands: immobilization of cell membrane fragments onto the surface of an open tubular capillary (OT columns) [7]. For example, OT columns were successfully used to immobilize cell membrane fragments with CB1/CB2 receptors and further for the identification of endocannabinoid receptor ligands from the extract of Zanthoxylum clava-herculis L. [34,47]. The development and the use of OT columns remain beyond the scope of this review and interested readers are encouraged to refer to other publications [7].…”
Section: The Use Of Cmacs In Identification Of Pharmacologically Actimentioning
confidence: 99%
“…For this purpose, fragments of cell membrane containing membrane protein bind non-covalently with a capillary using the avidin-biotin pair. Capillaries with immobilized P-glycoprotein (Moaddel et al, 2004), and recently with immobilized cannabinoid receptors (CB1/CB2) (Moaddel et al, 2011) were developed using this approach.…”
Section: If the Body Is Regarded As An Extremely Complex Chromatogrmentioning
confidence: 99%
“…These methods have been successfully used but predominantly to identify the most abundant compounds and not necessarily the most active. We have previously demonstrated that these issues can be addressed using bioaffinity chromatography and that this approach can be used for the isolation of active components from complex mixtures including tobacco smoke condensates and plant extracts [1014]. The previous studies have utilized cellular membrane affinity chromatography (CMAC) including CMAC columns containing single or multiple nAChR subtypes [15, 16].…”
Section: Introductionmentioning
confidence: 99%